Optimization of the Condition of Palm Frond Torrefaction Process by Utilizing Liquid Torrefaction Product as Pre-treatment for Improve Product Quality - Susanty, Wenny; Helwani, Zuchra; Bahruddin, Bahruddin (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2019)
AbstractPalm frond can be converted to solid fuel using torrefaction process as an alternative energy source. Torrefaction is the process to convert the biomass into solid fuel at a temperature range of 200-300oC in inert condition. Calorific value is the most important response in solid fuel. The aim of this research is to obtain the optimum condition of palm fronds torrefaction statistically was used Response Surface Methodology. Torrefaction of palm frond on fixed bed a horizontal reactor which is equipped with horizontal condenser and condensate trap with the condition process such as the temperature (225-275oC), time (15-45 min), and N2 flow rate (50-150 ml/min). This research methodology consist of drying, washing with liquid product of torrefaction, torrefaction, and analysis. The response variables were mass yield, calorific value, energy yield, and proximate. Design Expert Trial Version 7.0 Software was used for optimization of condition process with desirability. The optimized condition process were temperature of 275oC, time of 44 minute, and N2 flow rate of 50 ml/min.Keywords: solid fuel, design expert, optimization, palm frond, torrefaction